Протонна провідність та релаксаційні процеси в системі вода – пірогенний алюмокремнезем, модифікований поліетиленгліколем - Andriyko, L. S.; Zarko, V. I.; Gun'ko, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
The influence of surface modification of silica and alumina/silica with different content of alumina by poly(ethylene glycol), PEG, onto the relaxation processes in water clusters formed in 1% aqueous suspension was studied by thermally stimulated depolarization current method. It was shown that these processes are mainly affected by the modifier. Therefore, they are similar for 5% aqueous solution of PEG and PEG/nanooxide suspensions because of coverage of oxide nanoparticles by the polymer.